The Effect of Articulation Type Cooperative Learning Model on Students' Mathematical Concept Understanding - Juliyas Muharni, Lica Perta; Asria, Vingky Zulfa; Ali, Rini Hardiyanti (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This study stems from the low understanding of mathematical concepts among students and aims to examine whether there is a difference in understanding mathematical concepts between students who learn using the cooperative learning model of the articulation type and those who learn using the conventional learning model. The study employs a Quasi-Experimental design with a Pre-test Post-test Control Group Design, involving class VII.1 (experimental class) and VII.2 (control class) at SMP Babussalam Pekanbaru. The results of data analysis using a t-test showed that (2.98) (2.01) at a 5% significance level, leading to the acceptance of Hₐ. This demonstrates that the cooperative learning model of the articulation type significantly improves students' understanding of mathematical concepts compared to the conventional learning model, with the average score of the experimental class being higher than that of the control class.